Simulation of Fuzzy Logic Implementation in an IoT-Enabled Water Quality Monitoring System Using ESP8266 - Jaya, Indra; Nawawi, Muhammad; Hayati; Naila Eka Fazlin (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2026)
This research developed a water quality monitoring system using fuzzy logic and an ESP8266 microcontroller with temperature, humidity, pH, and Total Dissolved Solids (TDS) sensors. The system processes data in real time by converting sensor values ​​into linguistic categories, then produces water quality that meets WHO standards. The system is also connected to an IoT platform to facilitate remote monitoring. Simulation results show that the system is able to recognize overlapping water conditions, for example, at pH 7.5 which falls into the "Good" and "Medium" categories simultaneously with different weights. With sensor conditions of 28°C temperature, 65% humidity, pH 7.5, and TDS 400 mg/L, the system produces a quality score of 12.6, indicating excellent water quality. Field testing and comparison with laboratory results show an accuracy level of up to 92%. Fuzzy logic has proven to be more reliable than simple threshold methods, especially when conditions change rapidly or sensors experience shifts. However, the system's results are highly dependent on sensor calibration and regulations need to be adjusted to standards in each region. The computational limitations of the ESP8266 also mean that fuzzy processing must be done on a computer or in the cloud.